Characteristics and Simulation Biases of Corkscrew Sea Breezes on the East Coast of China. Issue 1 (3rd January 2019) - Lin, Yanluan; Cao, Dianbin; Lin, Namei; Xue, Wei; Xu, Shiming; Zhao, Yangyang; Li, Heng; Huang, Bin; Guo, Jianping
Abstract: Coastal areas, where sea breeze are prevalent, generally have good wind power resources and are favorable sites for wind farms. Corkscrew sea breezes, having greater wind power than backdoor sea breezes, dominate the local circulations in summer over the coastal area of Jiangsu province, China. Daily Weather Research and Forecasting simulations were conducted for the summer of 2012. Evaluations of 12 corkscrew sea breezes near the coast suggested that simulations captured the overall characteristics of wind changes with sea breezes, except an overestimate of wind speeds by up to 1 m/s at 10 m above ground level and a cold bias at night. Another prominent bias is the underestimated low‐level vertical wind shear at night. A representative corkscrew sea breeze in July 2012 was used to document the typical spatial structure and diurnal evolution of corkscrew sea breezes. Initiated at 1000 Local Standard Time (LST), the sea breeze reached its maximum strength at 1700 LST with an inland penetration depth of 70 km, an offshore extent up to 150 km, and a vertical extent of 500 m. The fully developed circulation was accompanied by a coastal jet with maximum winds up to 11 m/s 200 m above ground level. A series of sensitivity simulations indicated that simulated land‐surface temperatures and boundary‐layer mixing are the two key factors for low‐level wind simulation. Nocturnal stable boundary layer still remains a challenge for boundary layer schemes tested here. Key Points: Corkscrew sea breezes dominate local circulations in summer over the coastal area of Jiangsu, China WRF simulations have a cold bias and low level wind overestimate at night for 12 corkscrew sea breezes Land‐surface temperatures and boundary‐layer mixing are the two key factors for low level wind simulation